2007
DOI: 10.3200/aeoh.62.3.147-155
|View full text |Cite
|
Sign up to set email alerts
|

Sick Building Syndrome: Psychological, Somatic, and Environmental Determinants

Abstract: The authors aimed to examine potential relationships between work-related symptoms attributed to sick building syndrome (SBS) and certain psychological, somatic, and environmental factors. The multidisciplinary, cross-sectional study comprised 171 female subjects working in air-conditioned and naturally ventilated nonindustrial office buildings. The authors collected information concerning symptoms related to SBS and made assessments of quality of life by using appropriate questionnaires. They assessed the wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…Office work also unavoidably causes mental stress, which may play an intermediate role in causing LBP. 15 Studies have identified several individual factors associated with LBP in office workers, including older age, female sex, high body mass index, smoking, and previous symptoms. 3,16,17 Regarding work-related risk factors, more senior position, sitting for long hours, poor workstation ergonomics, and awkward working postures have been linked to increased risk of LBP.…”
mentioning
confidence: 99%
“…Office work also unavoidably causes mental stress, which may play an intermediate role in causing LBP. 15 Studies have identified several individual factors associated with LBP in office workers, including older age, female sex, high body mass index, smoking, and previous symptoms. 3,16,17 Regarding work-related risk factors, more senior position, sitting for long hours, poor workstation ergonomics, and awkward working postures have been linked to increased risk of LBP.…”
mentioning
confidence: 99%
“…The most common symptom is various in different studies; in some studies, the most common symptoms were headache, fatigue, and dry skin (4). While, in some other studies, weakness and fatigue are considered as the most common symptoms (5). According to the World Health Organization (WHO), the most common symptom of SBS is intellectual fatigue, but respiratory symptoms generally have the more frequency (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is also postulated that office workers who reported unacceptable indoor air quality may be exposed to sick building syndrome (Jaakkola and Miettinen 1995). Another plausible explanation of the findings is that a low satisfaction with the work environment condition may increase mental stress which plays an intermediate role in causing symptoms (Gomzi et al 2007). …”
Section: Wrist/hand Regionmentioning
confidence: 96%